Voltage Sag and Mitigation Using Dynamic Voltage Restorer (DVR) System - Wahab, Shairul Wizmar; Mohd Yusof, Alias (Faculty of Electrical Engineering, 2006)
This paper highlights voltage sag as one of a power quality issue and Dynamic Voltage Restorer (DVR) is using for mitigation of voltage sag. Voltage sag is short reduction voltage from nominal voltage, occurs in a short time which can cause damage and loss of production especially in industrial sector. Voltage sag always related with short circuit events and starting motor which draw very high lagging current. Since voltage sag is creating worse effects, the researchers almost keen to find the solutions for this problem. Nowadays, a lot of devices have been developed to mitigate voltage sag such as Dynamic Voltage Restorer (DVR), Distribution Static Compensator (D-Statcom) and Uninterruptible Power Supply (UPS). In this paper, focus is given only on DVR system which will be simulated by using PSCAD software in order to mitigate voltage sag. Mathematics model for calculation of voltage sag and voltage injection by DVR System also described.